Kenya : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report ;, 2008)
Kenya's macroeconomic performance continued to improve until violence erupted in the aftermath of the general elections of December 2007. This 2008 Article IV Consultation highlights that GDP growth reached 7.0 percent in 2007, the highest in more than two decades. Monetary policy was tightened in June 2008 to address rising inflation pressures. Executive Directors have welcomed the recent tightening of monetary policy and the authorities' readiness to tighten further to prevent the second-round effect of rising food and fuel prices.